Family support and functional independence among post-stroke patients - Sunarsih Sunarsih; Putik Octa Khotimi; Purwati Purwati; Sulastri Sulastri (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Stroke frequently causes persistent disability and dependence in activities of daily living. Family support may facilitate rehabilitation by reinforcing treatment adherence, daily activity practice, continuity of care, and psychosocial adjustment. Purpose: To examine the association between family support and functional independence among post-stroke patients attending a neurology outpatient clinic. Method: This cross-sectional analytic study included 71 post-stroke patients recruited through purposive sampling at the neurology outpatient clinic of Jenderal Ahmad Yani Metro Regional General Hospital. Data were collected from May 21 to May 31, 2025. Descriptive statistics summarized participant characteristics and study variables, and the chi-square test was used to assess the association between family support and functional independence. Results: High family support was the most frequently reported category, identified in 23 participants (32.4%), and 19 participants (26.8%) were classified as independent. Family support was significantly associated with functional independence (p = 0.002). Conclusion: Family support was associated with functional independence among post-stroke patients. Because of the cross-sectional design, the findings indicate an association rather than a causal effect.